2021
DOI: 10.1093/noajnl/vdab089
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in meningioma

Abstract: Meningiomas are the most common primary intracranial tumor in adults. Although frequently histologically benign, the clinical severity of a lesion may range from being asymptomatic to causing severe impairment of global function and well-being. The diversity of intracranial locations and clinical phenotypes poses a challenge when studying functional impairments, however, more recent attention to patient-reported outcomes and health-related quality of life (HRQOL) have helped to improve our understanding of how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 71 publications
(105 reference statements)
1
17
0
3
Order By: Relevance
“…Although meningiomas do not always cause neurological deficits or other symptoms, patients with meningiomas demonstrate significant impaired quality of life compared to normative healthy controls even before surgery (van Nieuwenhuizen et al, 2013;Haider et al, 2021). This may be partially attributed to disease-related stress, when a patient realizes that he or she has got a brain tumour, or to preoperative anxiety (Wagner et al, 2019;Haider et al, 2021).…”
Section: Quality Of Life and Functional Outcome After Aggressive Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Although meningiomas do not always cause neurological deficits or other symptoms, patients with meningiomas demonstrate significant impaired quality of life compared to normative healthy controls even before surgery (van Nieuwenhuizen et al, 2013;Haider et al, 2021). This may be partially attributed to disease-related stress, when a patient realizes that he or she has got a brain tumour, or to preoperative anxiety (Wagner et al, 2019;Haider et al, 2021).…”
Section: Quality Of Life and Functional Outcome After Aggressive Surgerymentioning
confidence: 99%
“…Although meningiomas do not always cause neurological deficits or other symptoms, patients with meningiomas demonstrate significant impaired quality of life compared to normative healthy controls even before surgery (van Nieuwenhuizen et al, 2013;Haider et al, 2021). This may be partially attributed to disease-related stress, when a patient realizes that he or she has got a brain tumour, or to preoperative anxiety (Wagner et al, 2019;Haider et al, 2021). Jakola et al (2012) prospectively evaluated a cohort of 54 patients with meningiomas and found an improvement of the cases' health related quality of life (HRQOL) after surgery, which was mainly due to relief from anxiety.…”
Section: Quality Of Life and Functional Outcome After Aggressive Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Overall health-related quality of life tends to improve in meningioma patients after treatment, regardless of modality (11). Studies have shown that degree of improvement is often related to severity of symptoms before treatment (12).…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring quality of life and everyday life from a patient perspective in patients with WHO grade 3 meningioma are non‐existing. In meningioma, irrespective of grade, recent studies found a long‐term reduction in health‐related quality of life, 103,104 elevated use of anti‐depressants even two years after surgery, 54 and a high burden of socioeconomic difficulties after meningioma surgery 105 . Moreover, patients with meningioma experienced a lack of support in the postoperative phase for optimal recovery 106 and could experience a paradox when they had to undergo extensive surgery for a benign tumour 107 .…”
Section: Introductionmentioning
confidence: 99%